A REVISION OF FACCHINIA (MINUARTIA S.L., CARYOPHYLLACEAE). (3rd November 2015) - Dillenberger, M. S.; Kadereit, J. W.
Abstract : Facchinia Rchb. (Alsinoideae–Caryophyllaceae), earlier found not to be part of Minuartia s.str., is here revised. The genus contains seven species, one of which has two subspecies. Seven new combinations are made: Facchinia cerastiifolia (Ramond ex DC.) Dillenb. & Kadereit, F. cherlerioides (Sieber) Dillenb. & Kadereit, F. cherlerioides subsp. aretioides (Port. ex J.Gay) Dillenb. & Kadereit, F. grignensis (Rchb.) Dillenb. & Kadereit, F. herniarioides (Rion) Dillenb. & Kadereit, F. rupestris (Scop.) Dillenb. & Kadereit, and F. valentina (Pau) Dillenb. & Kadereit. Keys to Minuartia s.str., the Old World segregate genera of Minuartia s.l., and to the species and subspecies of Facchinia are provided. All taxa are described and mapped, and some are illustrated.